Interpreting probability : controversies and developments in the early twentieth century - Howie, David, 1970- (Cambridge studies in probability, induction, and decision theory., 2002)
This book investigates how Bayesianism as one theory of probability was discredited during the 1920s and 1930s by two British scientists and shows how the choice of a certain interpretation of probability depends on the experiences of the individuals involved.